DESIGNING THE P.A.T ALPHABET TO SUPPORT TEACHING WRITING DESCRIPTIVE TEXT - Ramadanti, Rika Maudy; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research aims to design teaching materials by using PowerPoint Presentation to support teaching learning process of writing descriptive text about people, animal, and thing. The researcher took the topic based on the syllabus used in the school. The method of research is development research using ADDIE approach (Analyze, Design, Develop, Implement, and Evaluation) as the phases in designing the P.A.T Alphabet. The first three phases were used by researcher. The P.A.T Alphabet is a presentation application containing materials for teaching learning about descriptive text. The P.A.T Alphabet provides four main menus such as People(P), Animal(A), Thing(T), and Games. Each menu has different contents with full color layout, animation, and sounds. Assessment rubric of The P.A.T Alphabet contains 10 criteria with the result 34 points that indicate the application as Satisfactory. It means the application is acceptable for classroom use particularly in teaching learning the topic. Keyword: Instructional, PowerPoint, ADDIE, Writing. Abstrak: Penelitian ini bertujuan unutk merancang materi pembelajran dengan menggunakan PowerPoint Presentation untuk mendukung proses belajar dan mengajar menegenai teks deskriptif tulis tentang orang, binatang, dan benda. Peneliti mengambil topik berdasarkan silabus yang digunakan oleh sekolah. Metode penelitiannya adalah penelitian pengembangan menggunakan pendekatan ADDIE (analisis, merancang, mengembangkan, mengimplementasikan, dan evaluasi) sebagai fase dalam merancang The P.A.T Alphabet. Tiga fase pertama adalah tiga fase yang digunakan oleh peneliti. The P.A.T Alphabet adalah sebuah aplikasi presentasi yang berisi materi-materi untuk belajar dan mengajar mengenai teks deskriptif. The P.A.T Alphabet menyediakan empat menu utama seperti People (P), Animal (A), Thing (T), and Games. Setiap menu memiliki isi yang berbeda dengan tampilan penuh warna, animasi, dan suara. Rubrik penilaian dari The P.A.T Alphabet terdiri dari 10 kriteria dengan hasil 34 poin yang menunjukkan aplikasi tersebut memuaskan. Hal ini berarti aplikasi tersebut dapat diterima untuk penggunaan di dalam kelas terutama dalam pengajaran dan pembelajaran topik tersebut. Kata Kunci: Instruksional, PowerPoint, ADDIE, Menulis.